Suspension high velocity oxy-fuel (SHVOF) spray of delta-theta alumina suspension: phase transformation and tribology - Owoseni, T.A.; Murray, J.W.; Pala, Z.; Lester, Edward; Grant, David; Hussain, Tanvir (Elsevier, 2018)
Suspension high-velocity oxy-fuel (SHVOF) thermal spray is an emerging spray technology that enables the processing of nanometric feedstock. Although SHVOF thermal sprayed alumina coatings prepared from alpha alumina feedstock have been widely reported, a metastable δ-θ Al2O3 feedstock has yet to be investigated despite its low cost and commercial availability. In this study, an aqueous δ-θ Al2O3 suspension was sprayed on to a stainless steel (SS 304) substrate via SHVOF thermal spraying using an internal injection UTP TopGun. X-ray diffraction (XRD) of the as-sprayed coating showed δ-θ Al2O3 to γ-Al2O3 transformation upon spraying, along with amorphous/nanocrystalline phase formation. Furthermore, post-spray heat treatment of the coatings was performed at 600–750 °C for 6 and 48 h. The microhardness and indentation fracture toughness of the heat treated coatings increased by a factor of two compared to the as-sprayed coatings: due to grain refinement, pore consolidation and phase transformation of amorphous and γ-Al2O3 to δ-Al2O3. Unlubricated sliding wear tests were conducted at room temperature (~25 °C, relative humidity ~60%) using α-Al2O3 balls (Ø 9.5 mm) as the counter body at a normal load of 16.8 N to study the wear performance of the coatings. The wear rate of the as-sprayed coating and the coating heat treated at 600 °C for 6 h is of the order of 10−9 mm3 (Nm)−1, a noticeable improvement over conventional alumina coatings. The coatings heat treated at 750 °C for both 6 and 48 h failed abruptly by severe wear due to their pre-cracked surface.